2009
DOI: 10.1509/jmkg.73.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Internet Auction Features as Quality Signals

Abstract: Internet auction companies have developed innovative tools that enable sellers to reveal more information about their credibility and product quality to avoid the "lemons" problem. On the basis of signaling and auction theories, the authors propose a typology of Internet auction quality and credibility indicators, adopt and modify Park and Bradlow's (2005) model, and use eBay as an example to examine empirically how different types of indicators help alleviate uncertainty. This empirical evidence demonstrates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(19 citation statements)
references
References 65 publications
(109 reference statements)
0
14
0
4
Order By: Relevance
“…First, we establish price as a determinant of whether a buyer will approach or avoid a seller with incidentally similar characteristics. Second, while prior work has shown that explicit cues, such as the inclusion of item pictures (Li, Srinivasan, & Sun, 2009), might influence buyer intentions, we demonstrate that a more subtle, and thus far unexamined, social cueincidental similarity-might play an important role too. Specifically, we show that buyer behavior in online auctions can be affected by the degree of similarity between their own name and that of sellers.…”
mentioning
confidence: 43%
“…First, we establish price as a determinant of whether a buyer will approach or avoid a seller with incidentally similar characteristics. Second, while prior work has shown that explicit cues, such as the inclusion of item pictures (Li, Srinivasan, & Sun, 2009), might influence buyer intentions, we demonstrate that a more subtle, and thus far unexamined, social cueincidental similarity-might play an important role too. Specifically, we show that buyer behavior in online auctions can be affected by the degree of similarity between their own name and that of sellers.…”
mentioning
confidence: 43%
“…In an e-commerce context, many researchers have contended that buyers are willing to pay a price premium to high-reputation sellers because a high reputation may imply seller quality (Ba and Pavlou 2002; Li, Srinivasan, and Sun 2009), trustworthiness (Ba and Pavlou 2002; Bruce, Haruvy, and Rao 2004), and greater service quality (Luo and Chung 2010). Therefore, it is commonly believed that high-reputation sellers should charge relatively high prices (Ba and Pavlou 2002; Li, Srinivasan, and Sun 2009). However, some studies have identified a negative price premium effect (i.e., a high-reputation seller who charges a lower price than a low-reputation seller) in light of consumer informativeness and seller competition (Liu, Feng, and Wei 2012).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…When items are represented visually and not physically present, consumers face a higher level of uncertainty than in store (Dewally and Ederington, 2006). Information theory suggests that an increase in the number of photos used would be an indicator of quality that would limit information asymmetry (Milgrom and Roberts, 1986) and favourably increase behavioural responses (Li et al, 2009). The psychology literature on mental imagery provides an analytical framework that explains this process from the consumer's point of view.…”
Section: Literature Reviewmentioning
confidence: 99%